Support influence on the basicity promotion of lithium-based mixed oxides for transesterification reaction - Castro, Cinthia S. (2013)
Solid catalysts comprising Li-based oxides were prepared by LiNO3 impregnation onto supports with different acid/base properties (SiO2, MgO, Al2O3 and Mg(Al)O mixed oxide obtained from hydrotalcite). The materials were characterized by means of XRD, N2 physisorption, ICP?OES, FEG-SEM and TPD of CO2. The oxide reactivities were evaluated using the model transesterification reaction between methyl acetate and ethanol under mild reaction conditions (313 K, ethanol/methyl acetate molar ratio = 6/1 and 0.2 wt.% of catalyst). Lithium impregnation onto silica and c-alumina yielded inactive catalysts for transesterification. On the other hand, the lithium addition onto MgO produced an active catalyst and remarkably high conversions were obtained for Li/Mg(Al)O. The different supports used considerably affected the base site densities and base strengths of the Li-based catalysts. The base properties thus influenced the catalytic performance of the materials. Stability tests revealed the lithium leaching occurrence which resulted in some homogeneous contribution.